2023
DOI: 10.1007/s00018-023-04778-9
|View full text |Cite
|
Sign up to set email alerts
|

A neuroprotective role of Ufmylation through Atg9 in the aging brain of Drosophila

Abstract: Ufmylation is a recently identi ed small ubiquitin-like modi cation, whose biological function and relevant cellular targets are poorly understood. Here we present evidence of a neuroprotective role for Ufmylation involving Autophagy-related gene 9 (Atg9) in the aging brain of Drosophila. The Ufm1 system ensures the health of aged neurons via Atg9 by coordinating autophagy and mTORC1, and maintaining mitochondrial homeostasis and JNK (c-Jun N-terminal kinase) activity. Neuron-speci c expression of Atg9 suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…E3 UFM1-protein ligase mediates ufmylation of target proteins. Ufmylation is a recently identified small ubiquitin-like modification, whose biological function and relevant cellular targets are poorly understood 55 .…”
Section: Resultsmentioning
confidence: 99%
“…E3 UFM1-protein ligase mediates ufmylation of target proteins. Ufmylation is a recently identified small ubiquitin-like modification, whose biological function and relevant cellular targets are poorly understood 55 .…”
Section: Resultsmentioning
confidence: 99%
“…The mTOR, composed of two complexes (mTORC1 and mTORC2), regulates protein translation and cell growth by responding to a variety of environmental variables, such as growth factors, nutrition and energy [ 55 ]; phosphatidylinositol 3-kinase (PI3K)/Akt (Protein Kinase B) and AMPK are the major regulators of mTOR [ 56 ]. In agreement with the findings of the present study, several studies have found a significant effect of Al exposure on the protein expression of PI3K, Akt and mTOR, which are involved in neuronal plasticity [ 57 ], implying that increased Al exposure in the brain is accompanied by decreased expression of the mTOR signaling pathway, leading to neuronal damage and cognitive decline [ 58 ].…”
Section: Discussionmentioning
confidence: 99%